2018
DOI: 10.4149/neo_2018_170426n313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CALR and JAK2 mutations on the clinical and hematological phenotypes of the disease in patients with myelofibrosis – long-term experience from a single center

Abstract: Primary myelofibrosis (PMF) is a chronic clonal myeloid disorder. Together with essential thrombocythemia (ET) and polycythemia vera (PV), it belongs to a group of Philadelphia chromosome-negative myeloproliferative neoplasms. An integral part of laboratory tests carried out in this disease group is detecting the presence of mutations in the Janus kinase 2 gene at position 617 (JAK2 V617F) and in the gene encoding for the receptor for thrombopoietin (myeloproliferative leukemia virus oncogene, MPL) found in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…On the contrary, upregulation of pro-inflammatory cytokines was almost absent in serum of Ly6G-Cre CALR +/del mice. This is in line with the clinical observation of less frequent inflammatory symptoms of CALR mutated MPN patients [ 26 ]. Differential expression of TNFα protein in primary hematopoietic cell populations isolated from JAK2-V617F versus CALR mutant patients has also been described by Fisher and colleagues [ 88 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the contrary, upregulation of pro-inflammatory cytokines was almost absent in serum of Ly6G-Cre CALR +/del mice. This is in line with the clinical observation of less frequent inflammatory symptoms of CALR mutated MPN patients [ 26 ]. Differential expression of TNFα protein in primary hematopoietic cell populations isolated from JAK2-V617F versus CALR mutant patients has also been described by Fisher and colleagues [ 88 ].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, previous work has demonstrated that neutrophils and monocytes moving along and adhering to the endothelium provide the initiating stimulus for thrombosis development [ 101 103 ]. Hence, the observed differences in migration and adhesion between JAK2-V617F and CALRdel positive neutrophils aligns with the clinical observation that JAK2-V617F is the primary driving force of the pro-thrombotic risk in MPN whereas mutated CALR seems to have a lesser impact [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Mutations in the MPL lead to increased JAK/STAT activation, leading to downstream effects of changes in cytokines and growth factors that promote fibrosis. Mutations in the calreticulin gene (CALR) have also been seen in patients with PMF promoting similar downstream activation of the JAK/STAT pathway [ 10 - 11 ]. Overall, 90% of patients with PMF have the JAK2, MPL, or CALR mutation, which are mutually exclusive [ 12 ].…”
Section: Introductionmentioning
confidence: 99%